Meningkatkan Keterampilan Sholat Fardhu Dan Baca Al-Qur’an Melalui Metode Tutor Sebaya di SMPN 4 Lima Puluh Kabupaten Batu Bara - Junaidi Arsyad (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
ABSTRACTThe purpose of this research is to improve the learning process and Improve Fardhu Prayer Skill and Read al-Qur'an through Peer Tutor Method at SMPN 4 Lima Puluh Kabupaten Batu Bara. The method used in this research is qualitative research in the form of class action research (PTK), data pengumpualan technique that is by way of observation, questionnaires, documents and pasticipative. The stages of this research are cycles that include planning, implementation, observation, and reflection, and are implemented in two cycles. The result of the research proves that peer tutor method can improve the students' skill in performing fardhu prayer and read al-Qur'an in SMPN 4 Lima Puluh. The result of field observation shows that the fardhu and read al-Qur'an students' reading skills are improved, it can be seen from the post test of cycle I, that the percentage of completeness is 26,66% and post test of cycle II percentage is 93,33% The percentage of mastery increased by 66.67%. Thus the classical thoroughness requirement that is at least 85% of the total students reaching the value of ≥ 80 has been met. Keywords: Peer Tutor, Fardhu Prayer, Al-Quran